POINT DEFECTS IN CRYSTALLINE ZIRCON (ZIRCONIUM SILICATE), ZRSIO4: ELECTRON PARAMAGNETIC RESONANCE STUDIES - Tennant W.C.; Claridge R.F.C.; Walsby C.J.; Lees N.S. (My University, 2004)
This article outlines the present state of knowledge of paramagnetic defects in crystalline zircon as obtained mainly, but not exclusively, from electron paramagnetic resonance (EPR) studies in crystalline zircon (zirconium silicate, ZrSiO4). The emphasis is on single-crystal studies where, in principle, unambiguous analysis is possible. Firstly, the crystallography of zircon is presented. Secondly, the relationships between available crystal-site symmetries and the symmetries of observed paramagnetic species in zircon, and how these observations lead to unambiguous assignments of point-group symmetries for particular paramagnetic species are detailed. Next, spin-Hamiltonian (SH) analysis is discussed with emphasis on the symmetry relationships that necessarily exist amongst the Laue classes of the crystal sites in zircon, the paramagnetic species occupying those sites and the SH itself. The final sections of the article then survey the results of EPR studies on zircon over the period 1960–2002.
Keywords: Electron paramagnetic resonance; Point defects; Zircon